Evaluation the Compared Doppler Ultrasonography and Serial Fondal Height Measurement in Detection of IUGR - Shohreh Alimohammadi; Mehrangiz Zamani (پزشکی بالینی ابن سینا, 2008)
Introduction & Objective: There are different methods for detection of fetal growth restriction. The most important methods are serial fondal height (SFH), and ultrasonic measurement. The sensitivities and specifities of those methods are vary among different population, so, in a comparative study, we evaluated the sensitivity and specificity of SFH, a safe and simple method, and Doppler ultrasonography in F.G.R.